ANALISIS DU PONT SYSTEM UNTUK MEMPREDIKSI SUSTAINABILITY USAHA PADA PT BETONJAYA MANUNGGAL TBK PERIODE 2013-2017 - Astuti, Puput Yuliani; Suhardiyah, Martha (Fakultas Ekonomi Universitas PGRI Adi Buana, 2019)
This study aims to measure the company's financial performance by using the analysis of Du Pont System and to predict business continuity in a safe, vulnerable, or bankrupt condition by using Altman Z-Score calculations. This study uses a quantitative approach with descriptive and associative analysis methods. The results of this study indicate that the company's financial performance is in good condition in 2013 and 2017. The business continuity analysis using Altman Z-Score calculation shows that the condition of the company is healthy only in 2013, for 2014 to 2017 the condition of the company is in the gray area indicates that the company is in a vulnerable condition. The results of research with associative methods or statistical tests show that the analysis of Du Pont System can predict business continuity by using Altman Z-Score calculations. The implication of this research is that the Du Pont System analysis shows that the company's performance is unstable, and the sustainability analysis shows that the company in healthy condition occurred in 2013.